Aspectos termodinâmicos e cinéticos do uso de plugues porosos para a remoção de partículas cerâmicas por bolhas inteligentes - Falsetti, Luís Otávio Zaparoli (Universidade Federal de São Carlos, 2021)
Non-metallic inclusions can spoil the mechanical properties of the steel depending on their composition, geometry, size and distribution. In this context, “inclusion engineering” is a rising area in steelmaking industry which studies the modification and removal of ceramic particles from the molten steel. Among the likely tools to withdraw these inclusions, the generation of bubbles through purging plugs shows the advantage of allowing the high productivity demanded by the continuous casting. This process comprises the generation of bubbles, their expansion throughout the ladle, the capture of the ceramic particle and their transfer to the slag phase. Thus, understanding the fundamentals involved in each step is of great importance to master the bubbling in ladles aiming cleaner steels. The present work studied the current practice of steel cleaning using bubbles, analysing the size limits to the capture of ceramic particles and discussing alternatives to obtain cleaner steels. Besides, the infiltration of liquid metal into the porous structure was analysed to minimize the plug maintenance due to clogged metal. Therefore, computational calculations were carried out based on mathematical models for each step of purging plug practice, and the results were validated by comparison with physical simulations from the literature and the industrial practice.
Thermodynamic and kinetic aspects of the porous plugs practice aiming the removal of ceramic particles by smart bubbles
Keywords: Aços limpos; Inclusões não metálicas; Partículas cerâmicas; Plugues porosos; Infiltração em estruturas porosas; Clean steel; Non-metallic inclusions; Ceramic particles; Porous plugs; Porous structure infiltration; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS